PERLINDUNGAN HUKUM PENGGUNA JASA TRANSPORTASI UDARA AKIBAT DELAY MANAGEMENT MASKAPAI NIAGA BERJADWAL - Hafidz, Aufa Ahla; Widijowati, Dijan; Halim, Anriz Nazaruddin (Jurnal Penelitian Hukum Legalitas, 2023)
The Regulation of the Minister of Transportation Number PM 89 of 2015 concerning Handling of Flight Delays (Delay management) in Scheduled Commercial Air Transport Business Entities in Indonesia explains that airlines as air transportation service providers must pay a certain amount of compensation to passengers (consumers). However, in practice there is still management negligence on the flight, causing losses to passengers, due to delay management by the carrier. This research is a normative juridical research with a statutory approach, a case approach, a conceptual approach and an analytical approach. The source of legal materials in this study is only secondary data using the technique of collecting legal materials from literature. The analysis of legal materials used are grammatical, systematic, historical and teleological interpretations. The results show that the legal protection of air transportation service users in the event of flight schedule delays caused by airlines management factors, namely air transportation service users who are disadvantaged are entitled to compensation from the airline for flight delays that occur and also for losses that have been experienced. This is as stated in the Regulation of the Minister of Transportation Number 89 of 2015 concerning Handling of Flight Delays which can be proven by airplane tickets.